EFEKTIVITAS SEDIAAN SALEP EKSTRAK BUNGA KECOMBRANG (Etlingera elatior) TERHADAP PENYEMBUHAN LUKA INSISI PADA TIKUS (Rattus norvegicus) - Ratna Widyawati; Olan Rahayu Puji Astuti Mussa; Miarsono Sigit; Bernadeta Perwirawati Lepu Geli (VITEK : Bidang Kedokteran Hewan, 2019)
This study was conducted to determine the effect of ointment extract of kecombrang flower (Etlingera elatior) on healing incision wounds in white rats (Ratus norvegicus) in terms of the formation of wound scab, wound closure time and wound attachment. The experimental research used is Randomized complete design with 4 treatments with 6 replications. The treatments applied were P0 as a negative control, P1 (20% kecombrang flower extract ointment), P2 (30% kecombrang flower extract ointment) and P3 (40% kecombrang flower extract ointment). Parameters of this study were the wound caropeng, wound closure time and wound attachment. The results obtained were different median values in the four groups with p = 0,000 (p <0.05) in the Kruskal Wallis test. In the Mann Whitney test were significant differences between the groups of 20% kecombrang flower extract ointment concentration, 30% concentration and 40% concentration in the negative control group. The most effective result is ointment extract of kecombrang flower 20% on healing incision wounds.